Curcumin and Its Derivatives as Potential Antimalarial and Anti-Inflammatory Agents: A Review on Structure-Activity Relationship and Mechanism of Action - Siti Nur Hidayah Jamil; Amatul Hamizah Ali; Shevin Rizal Feroz; Su Datt Lam; Hani Kartini Agustar; Mohd Ridzuan Mohd Abd Razak; Jalifah Latip (MDPI AG, 2023)
Curcumin, one of the major ingredients of turmeric (Curcuma longa), has been widely reported for its diverse bioactivities, including against malaria and inflammatory-related diseases. However, curcumin's low bioavailability limits its potential as an antimalarial and anti-inflammatory agent. Therefore, research on the design and synthesis of novel curcumin derivatives is being actively pursued to improve the pharmacokinetic profile and efficacy of curcumin. This review discusses the antimalarial and anti-inflammatory activities and the structure-activity relationship (SAR), as well as the mechanisms of action of curcumin and its derivatives in malarial treatment. This review provides information on the identification of the methoxy phenyl group responsible for the antimalarial activity and the potential sites and functional groups of curcumin for structural modification to improve its antimalarial and anti-inflammatory actions, as well as potential molecular targets of curcumin derivatives in the context of malaria and inflammation.